The Effect of Increasing CO2 and Halyomorpha halys (Hemiptera: Pentatomidae) Damage on Plant Based ADEK Vitamins and Sterols - Özgen, İnanç; Kirmizikaya Özmen, Görkem; Buran, Abayhan; Sönmez, Ceyhan; Yilmaz, Kadir Görkem; Aydoğmuş, Ercan (ABADER (Adiyaman Bilimsel Arastirmalar Dernegi), 2026)
This study aims to evaluate the effects of global climate change on the nutritional content of agricultural products by examining the sucking pest Halyomorpha halys (Hemiptera: Pentatomidae) on pepper (Capsicum annuum L.), tomato (Solanum lycopersicum), and bean (Phaseolus vulgaris L.) plants at different feeding intensities and two different atmospheric carbon dioxide (CO2) levels (600 ppm and 670 ppm) on the ADEK vitamins and sterol components (µg/g) in leaf tissues. Experimental findings revealed that the levels of ?-tocopherol (vitamin E) and vitamin K2 showed significant differences depending on both the severity of the damage and the increase in CO2. In pepper groups, the amount of these compounds was high at low CO2 levels (600 ppm) but decreased at high CO2 levels (670 ppm). In contrast, vitamin E levels in tomato and bean groups decreased with increasing CO2. Sterol levels, specifically ergosterol and sitosterol, showed different responses depending on plant type with increasing CO2, while beta-sitosterol decreased significantly, especially at high damage levels. The results indicate that both biotic (pest) and abiotic (CO2) stress factors reorganise micronutrient and phytochemical compound levels in plants. These changes can be interpreted as adaptive physiological responses aimed at activating plant defence mechanisms and protecting cellular structure. The data obtained contribute to the development of strategies for preserving plant nutrient composition under climate change conditions. © 2026 ABADER (Adiyaman Bilimsel Arastirmalar Dernegi). All rights reserved.
Artan CO2 ve Halyomorpha halys (Hemiptera: Pentatomidae) Zararının Bitkisel ADEK Vitaminleri ve Steroller Üzerine Etkisi
Keywords: Capsicum annuum; climate change; Phaseolus vulgaris L; phytosterols; Solanum lycopersicum